Nutritional Quality of Three Cobitid Fishes of Manipur, India: With Special Reference to Essential Mineral Elements - Shantosh, M.; Sarojnalini, Ch. (International Journal of Scientific Research in Biological Sciences, 2018)
The study were carried out to determine the proximate composition and essential mineral elements of three Cobitid fish species of Manipur, India viz. Lepidochephalichthys guntea, Pangio pangia and Syncrossus berdmorei. Moisture (76.12±0.05 %) were significantly (p<0.05) higher in Pangio pangia. In Syncrossus berdmorei, significantly (p<0.05) higher protein (22.57±0.00 %) and lipid (12.93±0.66 %) were recorded. Whereas, ash (3.23±0.07 %) was significantly higher in Lepidochephalichthys guntea. Macro elements Ca, Mg, K and Na were abundantly found in all the fish studied and micro elements Mg, Ni Cu, Zn, and Fe were also found in adequate amount. Results from the analysis revealed that macro elements viz. Ca (2150±8.71 mg/100g) and Mg (131.7±2.05 mg/100g) and micro elements viz. Na (112.5±0.06 mg/100g), Ni (2.25±0.02 mg/100g), Cu (0.47±0.007 mg/100g) and Zn (3.05±0.014 mg/100g) were found significantly (p<0.05) higher in Lepidochephalichthys guntea. Whereas K (90.81±1.14 mg/100g) and Mn (1.26±0.01 mg/100g) were significantly (p<0.05) higher in Syncrossus berdmorei among the fishes studied. Fe content was recorded significantly (p<0.05) higher than other micro elements and found highest in Syncrossus berdmorei (28.61±0.10 mg/100g) amoung the fish studied. From the above analysis it has been reveal that all the fishes were good sources of protein, lipid, ash and mineral contents which can provide high nutritive value for human diet.